Scrutinizing EFL Teachers’ TPACK Mastery Level in Teaching English Based on Gender and Schools Status Disparities - Ince Rezky Naing; Pangesti Wiedarti (STAI Hubbulwathan Duri, 2023)
The existing technologies have profoundly influenced technology integration in teaching activities. However, integrating technology into English Language teaching is not entirely smooth since the teachers are not skilled in combining technology with content and pedagogy knowledge simultaneously in the learning process. Therefore, this study attempted to investigate the level of technological pedagogical content knowledge (TPACK) mastery from junior high school EFL teachers in Pangkajene and Kepulauan Regency based on teachers' gender and school status. The quantitative study with a survey method addressed the research's aim. The research conducted in Pangkajene and Kepulauan Regency involved 104 junior high school EFL teachers as research respondents. The data of this study were collected from in-service EFL teachers in public and private junior high schools by distributing the questionnaire offline and online. Version 26 of SPSS was employed to analyze the data. The analysis of the data encompassed inferential and descriptive statistics. The present study results elucidated that EFL teachers' TPACK mastery is in the very good category, with details of TK, TCK, PCK, and TPK in the very good category; CK and TPACK in the good category. Next, EFL teachers' TPACK mastery based on gender showed no significant difference in TPACK mastery between male and female teachers. Then, EFL teachers’ TPACK mastery based on school status showed no significant difference in TPACK mastery between teachers in public schools and private schools. These results imply that EFL teachers' TPACK knowledge and mastery are related to the proper implementation of ICT in classroom instruction.